PRE- FOUNDATION STUDIES USING VERTICAL ELECTRICAL SOUNDING AND SOIL SAMPLE ANALYSIS - Kazeem Oladimeji Olomo (Journal CleanWAS)
Subsurface rock properties investigation to categories foundation competent layer for the proposedengineered structure capable of housing offices, lecture halls, and laboratories was carried out usinggeophysical (GPHY) and geotechnical (GTECH) techniques. Electrical resistivity GPHY technique usingvertical electrical sounding (VES) field procedure was utilized in which nineteen (19) VES spots wereoccupied. Results of the VES revealed 2-D subsurface geoelectric sequences comprising of incompetentoverburden layer of about 5 m thick with resistivity value between 10 and 210 ohm-m typical of clay soilmaterial. Beneath this layer are sand formation and fresh bedrock with resistivity range of 750 to 1000 ohmm, which are good formations for foundation. Additionally, according to GPHY studies, western and northernportions of the region are marked by fractures/faults, which could cause building subsidence if foundation isstationed at these points. The results of the analyses of the soil samples taken in five different points in thestudy area revealed: (1) grain size distribution with 0.075 mm particle size passing of an average of 41%signifying the occurrence of clay, corroborating the presence of clay material within the weathered layer inGPHY investigations; (2) active and expansive nature of the soil with linear shrinkage greater than 8%revealing unsuitability of topsoil for foundation; (3) medium plasticity of soil indicating possible soil swelling;and (4) concomitant GTECH and GPHY results of the topsoil and weathered layer properties. The overburdenlayer with clayey materials must be removed and areas with geological structures must be taken into account.